Legal Services Corporation : Background and Funding. (U.S. Congressional Research., 2009)
Provides background and funding history of the Legal Services Corp. (LSC), a private, nonprofit, federally funded corporation that provides legal services to the poor. Examines program mechanics, including Congressional restrictions on LSC grantees; profiles clients and cases; and notes distribution of LSC funds and non-LSC resources.